2000
DOI: 10.1097/00005768-200005000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of exercise during road race pro-cycling competition

Abstract: Cycling is a high intensity sport because approximately 93 min in flat and 123 min in mountain stages were above 70% of VO2max. In addition, the time spent at IAT was roughly 20 min regardless of stage type, suggesting that the anaerobic capacity limits performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
3
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 13 publications
8
91
3
7
Order By: Relevance
“…A substantial number of scientific papers have been published describing the relationship exercise intensity and the effects of various CHO supplements during road cycling [19][20][21][22][23][24][25], but there are few scientific papers focused on the effect of maltodextrin supplementation in pre-competition or laboratory testing nor how it modifies off-road cycling performance parameters. Recent studies have found that carbohydrate drinks (glucose, maltose and sucrose administrated at 0.65 g/kg before a performance test and then 0.2 g/kg every 15 min during every 1 h of testing), when compared to a placebo (maltodextrin in low doses), increased plasma glucose levels but did not enhance performance during the test (a 1 h test) after glycogen-depletion protocol initiated [26].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of scientific papers have been published describing the relationship exercise intensity and the effects of various CHO supplements during road cycling [19][20][21][22][23][24][25], but there are few scientific papers focused on the effect of maltodextrin supplementation in pre-competition or laboratory testing nor how it modifies off-road cycling performance parameters. Recent studies have found that carbohydrate drinks (glucose, maltose and sucrose administrated at 0.65 g/kg before a performance test and then 0.2 g/kg every 15 min during every 1 h of testing), when compared to a placebo (maltodextrin in low doses), increased plasma glucose levels but did not enhance performance during the test (a 1 h test) after glycogen-depletion protocol initiated [26].…”
Section: Discussionmentioning
confidence: 99%
“…Professional road cycling is a remarkable endurance sport, composed of multiple-stage competitions of variable distance (5-300 km) and intensit 2max ) intensity, modera -2max 2max ) was 70%, 25%, and 5%, respectively (Fernández-García et al, 2000). Flat stages are covered predominantly at low-moderate intensity.…”
Section: Cycling Races and Performancementioning
confidence: 99%
“…For instance, high cardiovascular strain is evidenced by maintenance of high to near maximal HR (HR max ) during time trials (76%-94% HR max ), depending on the distance covered in the trial (Palmer et al, 1994(Palmer et al, , 1996. Furthermore, professional and amateur 2max values (70-80 ml·kg -1 ·min -1 ) (Coyle et al, 1991;Luciá et al, 1999;Fernández-García et al, 2000), and maximal power outputs (400-500 W) (Terrados et al, 1988;Wilber et al, 1997;Padilla et al, 1999). Time trials require cyclis 2max 2max ) through the majority of the race (Coyle et al, 1991;Luciá et al, 1999;Fernández-García et al, 2000); power outputs at these intensities approximate 350-400 W for high-level cyclists (Padilla et al, 1999(Padilla et al, , 2000.…”
Section: Cycling Races and Performancementioning
confidence: 99%
See 2 more Smart Citations